Postsecondary Systems, Massification, and the Research University - Altbach, Philip G. (International Higher Education, 2017)
In the context of massification, few countries have made any comprehensive effort to create clearly defined and differentiated academic systems to serve new academic functions. This pursuit is important to ensure quality and to meet the wide range of needs of an increasingly diverse student population.